Fungsi Cyber Public Relations Suku Dinas Komunikasi, Informatika dan Statistik Kota Administrasi Jakarta Selatan - Siena Gita Rahman; Lilik Sumarni (Institut Nalanda, 2025)
The development of communication technology, one of which is the internet has indirectly given birth to a form of virtual reality or the cyber world. This increasingly advanced information and communication technology directly encourages optimization in the role of public relations or public relations. Cyber ​​Public Relations is a form of Public Relations initiative in using internet media as a publicity effort. This research aims to determine Cyber ​​Public Relations using a descriptive qualitative approach method and cyber public relations theory proposed by Philps & Young (2009). Research data was obtained through primary data, namely interviews and secondary data from literature studies and observations. The research results show that in terms of transparency, the South Jakarta City Administration's Communications, Informatics and Statistics Department utilizes digital media such as websites and social media to convey accurate and easily accessible information. The concept of